Revisiting Education: On the Role of Imagination, Intuition, and Other “Gifts” for Open Scholars - Class, Barbara (Frontiers in Education, 2022)
The knowledge society is not a final state; rather, it is a collective task that we all must work towards. This reflective report, conducted in a Scholarship of Teaching and Learning approach by a scholar who teaches research methods and has been reflecting on research method education for a number of years, is a contribution to this endeavor. Its purpose is to share praxis, in the Freiran sense, on Open Education and Open Science as public good and commons through a specific example of Open Educational Practice (OEP). The report’s first finding involves documenting that OEP and providing some conceptual tools and suggestions for scholars who would like to move towards Openness. Its second finding, rooted in a previous SNSF research project, focuses on epistemology to raise awareness on the importance of philosophical and historical approaches to education. Without this knowledge, scholars find themselves closed in models that they replicate without consciously considering the values and methods they convey. The report’s third finding is a model of the knowledge creation process that considers knowledge as commons and incorporates a theoretical framework of absences and emergences that encompasses ignorance, inspiration, imagination, creativity, and intuition. Einstein called these faculties “gifts,” and we argue that scholars should learn to leverage them within an overall open framework.